A Framework for Improving 'Sales and Operations Planning'. Issue 1 (January 2014) - Kumar, Rakesh; Srivastava, Samir K.
Sales and Operations Planning (S&OP) initially came to existence in manufacturing in the late 1980s and has been around for about three decades now. It is the long-term collaborative planning process of production levels relative to sales within the realm of a manufacturing planning and control system at the Stock Keeping Unit (SKU) level. S&OP has evolved into a major business process adopted to manage the balance and trade-off between the conflicting preferences of the supply and demand side of the supply chain and offers many value creation opportunities. It is one of the most critical business processes used to achieve best in class performance to consistently outperform competitors. It is increasingly being viewed as essential to synchronise the entire supply chain in order to improve its efficiency, as once the S&OP process is institutionalised, it will enhance supply chain efficiency in the long run. It will also help the supply chain partners to understand and overcome supply chain risks resulting from market volatility. For this, firms must develop and deploy excellent leadership capabilities so that S&OP processes are in place and supported well within and across the supply chain. Although easy to understand, S&OP can be difficult to implement. Explaining the importance and working of S&OP, defining the key S&OP objectives and the role of people, process and technology, this article tries to address many evolving S&OP related operational issues from the people, process and supply chain perspective. It also prescribes practical ways to improve and institutionalise a strong S&OP process within a firm and consequently across the supply chain. Thereafter, it provides a useful framework to forecast ownership and suggests as to what should be discussed in S&OP meetings. Finally, it highlights the need to align the plans on a continuous basis and suggests a framework for the same.